Application of biochar from palm oil plants residues on physical properties of Ultisol - Irfan Rusdi; abdul Rauf; Supriadi Supriadi; Benny Hidayat (AGRITROPICA : Journal of Agricultural Sciences, 2019)
Ultisol is one type of soil that has several problems for plant growth. The main problems are poor physical properties such as high bulk density, low soil permeability, and low water retention ability. This research aim was to determine the effects of various application of biochar made of oil palm plants residue on bulk density and soil porosity of Ultisol soil. The research design used a non-factorial completely randomized design, consisting of 5 treatments, namely without biochar application (control), oil palm stem biochar, oil palm frond biochar, oil palm empty fruit bunches biochar and combination of biochar ingredients. Each treatment was repeated 4 times hence the number of experimental units became 20 units. The parameters observed included bulk density and soil porosity. The research results showed that biochar application significantly reduced the bulk density and significantly increased the soil porosity of Ultisol soil.